1979
DOI: 10.1094/phyto-69-27
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas corrugate, a Pathogen of Tomato, Isolated from Symptomless Alfalfa Roots

Abstract: Pseudomonas corrugata, the causal agent of a serious disease of roots, rotted onion scales and produced necrotic lesions on lettuce leaves, greenhouse-grown tomato plants in England, was isolated from healthy but potato tuber tissue was not rotted. Attempts to isolate strains of the roots of greenhouse-grown alfalfa plants in the USA. Inoculations of organism from field-grown alfalfa plants failed. Therefore, its role in root bacterial strains from both alfalfa and tomato into tomato stems induced and crown di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…Scarlett et al (1978) reported that P. corrugata did not rot onion slices. On the other hand, in the test of Lukezic (1979) this bacterium was capable of rotting onion sections if inoculated onto a cut surface. As regards P. marginalis (sensu stricto), this fluorescent pseudomonad serves as a typical species indicating the positive pectolytic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Scarlett et al (1978) reported that P. corrugata did not rot onion slices. On the other hand, in the test of Lukezic (1979) this bacterium was capable of rotting onion sections if inoculated onto a cut surface. As regards P. marginalis (sensu stricto), this fluorescent pseudomonad serves as a typical species indicating the positive pectolytic activity.…”
Section: Discussionmentioning
confidence: 98%
“…1988) and chrysanthemum with pith necrosis (Fiori 1992), in biochemical characteristics as well as in pigment prosoil (Scortichini 1989), water (Scarlett et al 1978), sympduction and colony morphology (Siverio et al 1993). High tomless alfalfa roots (Lukezic 1979), and wheat rhizosphere heterogeneity was also observed in reactions to three antisera (Roberts and Brewster 1991). It can cause significant losses, and the presence of at least 11 lipopolysaccharide profiles but particularly in tomatoes grown in unheated greenhouses no correlation to the origin of isolation was reported (Siverio where a great difference in temperature between night and et al 1993).…”
Section: Introductionmentioning
confidence: 95%
“…corrugata has already been described as closely related to some fluorescent pseudodifferent biochemical protein profile or react with different antisera. Despite the variability observed among strains, the monads on the basis of its phenotypic characteristics (Lukezic 1979), DNA-rRNA homology (De Vos et al 1985) and fatty phenotypic characteristics of Ps. corrugata clearly distinguish this group from other species.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…It is not uncommon that the explant material can harbor internal microorganisms (Armstrong, 1973;Tabor et al, 1991;Misaghi & Donndelinger, 1990;Petit et al, 1968;Gagne et al, 1987;Philipson & Blair, 1957;Lukezic, 1979;Sanford, 1948;DeBoer & Copeman, 1974;Hollis, 1951;Sturdy & Cole, 1974;Meneley & Stanghellini, 1974, 1975Samish et al, 1963;Bugbee et al, 1987;Tervet & Hollis, 1948;Knauss & Miller, 1978;DePrest & Van Vaerenbergh, 1980;Schreiber et al, 1996). When this is the case, it can be very difficult to establish clean cultures.…”
Section: Internal Microbial Contaminationmentioning
confidence: 99%